2015
DOI: 10.1097/aog.0000000000001068
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Influenza Vaccination and Risk for Congenital Malformations

Abstract: This systematic review did not indicate an increased risk for congenital anomalies after maternal influenza immunization adding to the evidence base on the safety of influenza vaccination in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…For example, at the time of the WHO position paper in 2012, a synthesis of the available evidence found no elevated risk of adverse fetal or neonatal outcomes associated with maternal influenza immunization [159]. More recently, three systematic reviews conducted updated analyses of safety studies published since the WHO position paper and detected no increased risk of spontaneous abortion [111], fetal death or stillbirth [110,111], preterm birth [110], or congenital anomalies [111,160] among pregnant women that received influenza vaccine. In fact, as noted previously, some studies have found that maternal influenza immunization was actually associated with a decreased risk of stillbirth [112] or preterm birth [105,113117].…”
Section: Clinical Aspects Of Maternal Influenza Immunizationmentioning
confidence: 99%
“…For example, at the time of the WHO position paper in 2012, a synthesis of the available evidence found no elevated risk of adverse fetal or neonatal outcomes associated with maternal influenza immunization [159]. More recently, three systematic reviews conducted updated analyses of safety studies published since the WHO position paper and detected no increased risk of spontaneous abortion [111], fetal death or stillbirth [110,111], preterm birth [110], or congenital anomalies [111,160] among pregnant women that received influenza vaccine. In fact, as noted previously, some studies have found that maternal influenza immunization was actually associated with a decreased risk of stillbirth [112] or preterm birth [105,113117].…”
Section: Clinical Aspects Of Maternal Influenza Immunizationmentioning
confidence: 99%
“…Background rates of spontaneous abortion vary from 10.4% in women aged <25 years to 22.4% in women aged >34 years (319); considering the number of pregnant women vaccinated, miscarriage following (but not attributable to) influenza vaccination would not be an unexpected event. Preliminary (as yet unpublished) results of a VSD study suggested an increased risk for spontaneous abortion in some pregnant women in the 1 to 28 days after receiving IIV3 during either the 2010-11 or the 2011-12 seasons; the increased risk was seen primarily in women who had also received a H1N1pdm09-containing vaccine in the previous season (320) A systematic review and meta-analysis of studies of congenital anomalies after vaccination including data from 15 studies (14 cohort studies and one case-control study), eight of which reported data on first-trimester immunization showed that risk for congenital malformations was similar for vaccinated and unvaccinated mothers: in the cohort studies, events per vaccinated versus unvaccinated were 2.6% versus 3.1% (5.4% versus 3.3% for the subanalysis involving firsttrimester vaccination); in the case-control study, the percentage vaccinated among cases versus controls was 37.3% versus 41.7% (325). There was no association between congenital defects and influenza vaccination in any trimester (OR: 0.96; 95% CI = 0.86-1.07) or specifically in the first trimester (OR: 1.03; 95% CI = 0.91-1.18).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
“…A limitation of many of these studies is the heterogeneity in the definitions used for birth defects across studies, and the limited number of studies where the vaccine was given during the first trimester. For many studies, the relatively small sample size of pregnant women makes it difficult to assess for specific birth defects, which tend to be rare (Polyzos et al, ; McMillan et al, ). Efforts to develop harmonized case definitions and guidelines for data collection and analysis of birth defects as an adverse event after vaccination have resulted in the development of definitions which will help investigators working with immunization safety data (DeSilva et al, ).…”
Section: Discussionmentioning
confidence: 99%